Analysis of the Effects of Physical Special Allocation Funds and Government Expenditures in Education on Economic Growth and Human Resource Quality - Cahyani Novianti, Ardiah Salsabila; Wildan Syafitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Unequal economic development is reflected in economic growth between regions, which gives rise to gaps in the quality of human resources. This study aims to determine the influence of Physical Special Allocation Funds and Regional Expenditures in the Education Sector on increasing Economic Growth and the Quality of Human Resources, focusing on the education sector as one of the main pillars of development. The methodology used in this research is panel data regression analysis by combining cross-section data from 38 districts/cities with time-series data for three years, namely from 2020 to 2022. The findings of this research show that special physical allocation funds have a positive and significant effect on economic growth and the quality of human resources. In contrast, regional spending in the education sector has a considerable influence, with a negative correlation between financial development and the quality of human resources. The implications of this research provide policymakers insight regarding optimizing public funds' use to support equality. Keywords: Physical Special Allocation Fund, Regional Expenditure in the Education Sector, Economic Growth, Human Resource Quality